Implementasi Tujuan Hukum Keadilan terkait Pemenuhan Hak Saksi Korban terhadap Barang Milik Pribadi pada Kasus Kejahatan Pencurian di Kota Makassar - Zaenudin Agus Binarto; Tri Syafari; Nam Rumkel (Khairun Law Journal, 2019)
Human longing for justice is essentially a longing for happiness, so efforts to fulfill various rights as witnesses of victims of theft crimes in Makassar City as a place of research have been conducted since 2017,2018 and 2019, actually show that the handling is carried out by the Police and the Prosecutor's Office especially in the victim's items found in the Police as well as the number of victim's items returned at the Prosecutor's Office, must be an important concern, but in fact, that victims of theft crimes are not like that .. This can be reflected in decisions by judges based on in the data in the last three years above, which convicted the perpetrators with imprisonment but none of the perpetrators were convicted to pay compensation to the victims. If the judge has the courage to make legal breakthroughs by punishing the perpetrator to pay compensation in the amount of the loss suffered by the victim, then, to be able to implement the legal objectives of justice related to the fulfillment of the victim's witness rights to personal property in a theft crime case can be realized